2010
DOI: 10.3324/haematol.2009.010736
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells in co-culture with mesenchymal stromal cells - modeling the niche compartments in vitro

Abstract: The online version of this article has a Supplementary Appendix. BackgroundHematopoietic stem cells located in the bone marrow interact with a specific microenvironment referred to as the stem cell niche. Data derived from ex vivo co-culture systems using mesenchymal stromal cells as a feeder cell layer suggest that cell-to-cell contact has a significant impact on the expansion, migratory potential and 'stemness' of hematopoietic stem cells. Here we investigated in detail the spatial relationship between hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(170 citation statements)
references
References 38 publications
11
151
1
7
Order By: Relevance
“…Many groups have shown that co-culture of leukemic cells with BMSC or OB provides a survival advantage when challenged with chemotherapy agents 9,10,[12][13][14][19][20][21] . Work modeling normal immature CD34+ hematopoietic cells in coculture with mesenchymal stem cells (MSC) revealed that hematopoietic cells will interact with the adherent monolayer of MSCs to form three distinct spatial populations of hematopoietic cells 22,23 . Proliferation and differentiation of the CD34+ cells was effected relative to their location within the co-culture 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many groups have shown that co-culture of leukemic cells with BMSC or OB provides a survival advantage when challenged with chemotherapy agents 9,10,[12][13][14][19][20][21] . Work modeling normal immature CD34+ hematopoietic cells in coculture with mesenchymal stem cells (MSC) revealed that hematopoietic cells will interact with the adherent monolayer of MSCs to form three distinct spatial populations of hematopoietic cells 22,23 . Proliferation and differentiation of the CD34+ cells was effected relative to their location within the co-culture 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Work modeling normal immature CD34+ hematopoietic cells in coculture with mesenchymal stem cells (MSC) revealed that hematopoietic cells will interact with the adherent monolayer of MSCs to form three distinct spatial populations of hematopoietic cells 22,23 . Proliferation and differentiation of the CD34+ cells was effected relative to their location within the co-culture 22 . We have expanded on this observation to test questions related to bone marrow microenvironment stromal cell support of a resistant population of tumor cells within a 2D co-culture and its isolation for downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, MSC have also been shown to be effective when sourced from other tissues including human placenta , umbilical cord (Bakhshi et al, 2008, Huang et al, 2007, Wang et al, 2004 and adipose tissue (Nakao et al, 2010). Recent papers have demonstrated that many of the specific cell-cell interactions between HSC and stromal cells are critical and may be essential for HSC regulation both in vivo (Steiner et al, 2009) and in vitro (Jing et al, 2010, Song et al, 2010, Wagner et al, 2008, Wagner et al, 2007, Wein et al, 2010. Indeed, a majority of studies have shown that cell-cell contact between HSC and MSC is essential for their ex vivo expansion.…”
Section: Preclinical and Clinical Studies Using Cord Blood Hscmentioning
confidence: 99%
“…Both of the mechanisms can be involved. The authors succeeded showing that predominantly CD34 + CD38 -HSCs migrate across the MSCs layers [57].…”
Section: Cd38mentioning
confidence: 91%